CORRIGENDUM to "Psychological, physical and sexual violence against children in Australian community sport: frequency, perpetrator and victim characteristics". (Journal of Interpersonal Violence, 2026)
The article addresses a statistical error identified in a previous analysis regarding the prevalence of psychological, physical, and sexual violence against children in Australian community sports. The error involved a coding mistake that misclassified instances of physical violence by coaches as psychological/neglect and vice versa, affecting specific tables and findings in the original paper. The authors provide corrected figures for the affected tables and clarify that while the error altered some data, it did not impact the overall claims made in the study. They express their apologies for the oversight.